2022
DOI: 10.1093/tropej/fmac006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics on the Frequency of CD4+ T-Cells in HIV-Infected Children and Adolescents: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background Depletion of CD4+ T-cells in the gut-associated lymphoid tissue is the hallmark of HIV infection, with only partial restoration by potent antiretroviral therapy (ART). Gut dysbiosis, together with disruption of mucosal integrity contributes to chronic immune activation that further exacerbates the disease. Data from randomized controlled trials in pediatric HIV patients have indicated potential of probiotics in complementing routine ART in managing HIV-associated gastrointestinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The predicted pooled MD of CD4 count following supplementation was only beneficial in children but not among adults. These findings were consistent with the trend in included primary studies [16,34,47], as well as in a previously published review paper [25]. One potential explanation is biological variation [52].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predicted pooled MD of CD4 count following supplementation was only beneficial in children but not among adults. These findings were consistent with the trend in included primary studies [16,34,47], as well as in a previously published review paper [25]. One potential explanation is biological variation [52].…”
Section: Discussionsupporting
confidence: 92%
“…Recently published meta-analyses focused on adults reported that probiotics had no effect on CD4 lymphocyte counts [22][23][24]. One metaanalysis of studies among children and adolescents only found that probiotics improved CD4 lymphocyte counts [25]. These meta-analyses did not however consider the HAART status of the participants and duration of probiotic supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenomic data on metformin absorption and excretion added an important tool to predict patients' responses to the presence of metformin, and how this could impact microbiota. The role of probiotics and prebiotics as adjuvants to the antidiabetic action of metformin through the modulation of the intestinal microbiota has been widely studied, while its impact on HIV infection 316 and neurodegenerative diseases 317 is still under debate, thus more studies would be necessary. The understanding of the interplay of so many factors on patients' outcome for several diseases is highly complex, and more correlations should be explored.…”
Section: Discussionmentioning
confidence: 99%